The cognitive challenge of war : Prussia 1806 - Paret, Peter (Princeton University Press, 2009)
Responding to the enemy's innovation in war presents problems to soldiers and societies of all times. This book traces Napoleon's victory over Prussia in 1806 and Prussia's effort to recover from defeat to show how in one particular historical episode operational analyses together with institutional and political decisions eventually turned defeat to victory. The author moves from a comparative study of French and Prussian forces to campaign narrative and strategic analysis. He examines processes of change in institutions and doctrine, as well as their dependence on social and political developments, and interprets works of art and literature as indicators of popular and elite attitudes toward war, which influence the conduct of war and the kind and extent of military innovation. In the concluding chapter he addresses the impact of 1806 on two men who fought on opposing sides in the campaign and sought a new theoretical understanding of war--Henri Jomini and Carl von Clausewitz. Fields of history that are often kept separate are brought together in this book, which seeks to replicate the links between different areas of thought and action as they exist in reality and shape events.